PERBANDINGAN KARAKTER NASIONALIS ANTARA SISWA YANG BERETIS TIONGHOA DENGAN SISWA ETNIS MELAYU KELAS XI SMA NEGERI 2 DABO SINGKEP TAHUN PELAJARAN 2013-2014 - Nurmi Vadilah Vadilah; Zahirman '; Hambali ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research background by the nationalist flavor differences between ethnic Chinese students with students who are ethnic Malays, who are ethnic Malay necessarily use basic characteristics in daily life the character of nationalism. However, students who are ethnic Chinese have a different character is a character that is still used strictly in the household environment and daily life. Vocabulary of the language is very different from the Indonesian. So writer take the title